2003
DOI: 10.1093/milmed/168.11.922
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Knowledge about Continuous Oral Contraceptive Pill Use in Military Women

Abstract: Although a significant number of soldiers desire OCP-induced amenorrhea, a large deficit in knowledge exists. Routine education as an Army-wide standard is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…In 2003, Powell-Dunford et al 31 estimated that 84% of female active duty U.S. Army personnel had a desire for temporary amenorrhea. Another study found 66% of female cadets at the U.S. Army Military Academy stated that their menstrual symptoms interfered with their physical activities, 32 suggesting a strong desire for temporary amenorrhea.…”
Section: Discussionmentioning
confidence: 99%
“…In 2003, Powell-Dunford et al 31 estimated that 84% of female active duty U.S. Army personnel had a desire for temporary amenorrhea. Another study found 66% of female cadets at the U.S. Army Military Academy stated that their menstrual symptoms interfered with their physical activities, 32 suggesting a strong desire for temporary amenorrhea.…”
Section: Discussionmentioning
confidence: 99%
“…This was surprising given the moderating effect of OC on menstrual symptoms and the belief that continuous use may improve quality of life (Wiegratz et al, 2004) and can be effective in terms of mediating menstrual symptoms (Edelman et al, 2005;Powell-Dunford et al, 2003). Over 80% of all women were interested in receiving education about continuous OC use.…”
Section: Discussionmentioning
confidence: 99%
“…The demographic, menstrual history, and OC knowledge and attitudes questions had been used in a previous study (Powell-Dunford et al, 2003). Menstrual concern was assessed through nine questions specific to menstrual symptoms and experiences during deployment: they were formatted as a 10-point Likert-type scale from least to greatest degree of symptomatology.…”
Section: Questionnaire Developmentmentioning
confidence: 99%
“…Menstrual hygiene is a burden in the field setting (Czerwinski et al. 2001, Wardell & Czerwinski 2001, Powell‐Dunford et al. 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In the only study that assessed military women’s attitudes towards menstrual suppression, it was found that the majority of women desired amenorrhoea during deployment, but few would choose to suppress menstruation with oral contraceptives (OCs) (Powell‐Dunford et al. 2003).…”
Section: Introductionmentioning
confidence: 99%